2012
DOI: 10.3922/j.psns.2012.1.09
|View full text |Cite
|
Sign up to set email alerts
|

Executive demands of the Tower of London task in Brazilian teenagers.

Abstract: Some executive tasks may require diverse abilities to solve, having implications for the comprehension of an individual's performance. This study investigated the processes involved in the resolution of a complex test of executive function (EF): the Tower of London (ToL) task. One hundred twenty-four healthy teenagers, 11-14 years old (M = 12.5, SD = 1.14) participated in the study. They were tested using the Auditory Working Memory Test, Visual Working Memory Test, Computerized Stroop Test, Semantic Generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
(86 reference statements)
0
6
0
5
Order By: Relevance
“…There are studies that, on the contrary, have clearly identified differences regarding gender (De Luca et al, 2003;Dias & Seabra, 2012). Thus, further research, especially with wider samples, is needed in order to clarify this matter.…”
Section: Discussionmentioning
confidence: 92%
“…There are studies that, on the contrary, have clearly identified differences regarding gender (De Luca et al, 2003;Dias & Seabra, 2012). Thus, further research, especially with wider samples, is needed in order to clarify this matter.…”
Section: Discussionmentioning
confidence: 92%
“…This task is an adaptation of the Wisconsin Card Sorting Test (WCST) and measures complex 170 executive functioning such as planning, cognitive flexibility, response inhibition, numerical skills 171 and rules induction[62]. Participants were required to categorize cards based on the pattern 172 appearing on them (seeFig.1).…”
mentioning
confidence: 99%
“…Embora haja a necessidade de desenvolver pesquisas nesse campo, existem diferentes instrumentos utilizados no Brasil para avaliar as funções cognitivas de atenção e executivas. No caso da avaliação da atenção sustentada para materiais visuais podemos citar o Teste de Cancelamento (TAC; Capovilla & Dias, 2008;Dias, 2009;Dias & Seabra, 2012;Hazin et al, 2012;Pereira et al, 2011;Seabra & Dias, 2010) e os Testes de Cancelamento -Figuras Geométricas e Letras em Fileira (Lima et al, 2009;Simão et al, 2010).…”
unclassified
“…Para avaliar os diferentes componentes das FE, outros instrumentos também são citados com paradigmas semelhantes, porém com estímulos ou versões diferentes: (a) Teste das Trilhas para avaliar atenção sustentada visual (Parte A) e fl exibilidade (Parte B; Dias & Seabra, 2012, 2014Lima et al, 2009;Simão et al, 2010); (b) Torre de Londres (ToL) para avaliar planejamento e raciocínio lógico (Dias & Seabra, 2012;Lima et al, 2009;Simão et al, 2010); (c) Teste de Fluência Verbal (FAS) para avaliar a fl uência verbal (Dias & Seabra, 2014); (d) Teste Cor-Palavra de Stroop (SCWT) para avaliar o controle inibitório e atenção seletiva (Charchat-Fichman & Oliveira, 2009;Dias & Seabra, 2012;Duncan, 2006;Lima et al, 2009;Simão et al, 2010).…”
unclassified
See 1 more Smart Citation